Azab Penghuni Neraka dalam Al-Qur’an Menurut Tafsîr Al-Marâghî - Karima, Litakuna; Amrulloh, Muhamad; Saputra, Akhmadiyah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research examines of punishment in hell according to Ahmad Musthafa al-Maraghi. Tafsir Maraghi, as one of the contemporer exagesis known for its explicit and in-depth approach to the Quran, provides valuable insights into this theme. This research aims to analyze the concept of hell punishment for its dwellers according to Tafsir Maraghi, focusing on the interpretation of relevant Quranic verses. The analysis results indicate that Tafsir Maraghi emphasizes the consequences of evil deeds in human life and their consequences in the hereafter, namely the punishment of hell. This punishment is severe and inevitable for those who commit sins and do not repent. Tafsir Maraghi also describes various forms of punishment experienced by the dwellers of hell, such as the torment of fire and the torment of boiling water, and emphasizes the importance of avoiding sinful acts and repenting to Allah as an efforts to avoid such punishment. This research is expected to contribute to a deeper understanding of the punishment in hell for its dwellers in Islam, particularly through the perspective of Tafsir Maraghi. The findings of this research are also expected to serve as a useful reference for academics, researchers, and practitioners interested in the conciseness of exegesis and Islamic studies